Analysis of Patriarchy in Hanna Lynn’s Athena’s Child - Anita Mardiana; Ambar Andayani (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
In patriarchal society, men are in a superior position than women. In this society men should be in charge and women should follow along, this causes women to be placed in a subordinate or inferior position. Patriarchy is important to discuss because Patriarchy is a socially-constructed system where males have primary power. It affects many aspects of life, from political leadership, business management, religious institutions, economic systems and property ownership, right down to the family home where men are considered to be the head of the household. The aims of the research are to analyze the reflection, the patriarchal systems portrayed and the effects of patriarchy on the victims in the novel. The literary work that is used in this research is Hanna Lynn’s Athena’s Child. This novel is based on the famous Greek mythology retelling of the story of Medusa. This research is conducted by using qualitative method and library research. The analysis is based on the theory of the Patriarchy’s by Allan G. Johnson and Sylvia Walby’s patriarchal structures. The research shows patriarchal system that occurs in the novel entitled Athena’s Child by Hanna Lynn and the effect to the victims.